Investigation on stimulated Brillouin scattering characteristics in a highly doped Bismuth-based Erbium-doped fiber - Parvizi, R.; Harun, Sulaiman Wadi; Ali, N.M.; Ahmad, Harith (IOP Publishing, 2010)
Stimulated Brillouin scattering (SBS) characteristics in a 49 cm long highly doped Bismuth-based Erbium doped fiber (Bi-EDF) is investigated in the ring and linear cavity configurations. At Brillouin pump (BP) power of 6 dBm, the Brillouin laser peak power of the optimized ring Brillouin Erbium fiber laser (BEFL) is obtained at 23 dB higher than the peak power of the conventional linear cavity at an up shifted wavelength of 0.08 nm. This Bi-EDF ring cavity operates at nearly 1563 nm wavelength region, which is up-shifted by 0.08 nm from the Brillouin pump wavelength with the side mode suppression ratios (SMSR) of 29 and 23 dB in the forward and backward directions, respectively.